PENGARUH DIRECT MARKETING, SALES PROMOTION DAN PERSEPSI HARGA TERHADAP MINAT BELI KONSUMEN (Studi Kasus Pada Pengguna Paket Data Internet Indosat Ooredoo Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Aji Kusnandri; Muhammad Mansur; M. Hufron (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACKT This study aims to determine and analyze the effect of direct marketing, sales promotion, and price perception both simultaneously and partially on consumer buying interest in the Indosat Ooredoo internet data package. The method used in sampling is non-probability sampling, which is a purposive sampling technique in which the sample determination technique takes into consideration certain criteria. The analytical technique used is quantitative descriptive using a Likert scale, multiple linear regression analysis, coefficient of determination and also through f test and t test using the SPSS program.Based on the results of data analysis simultaneously shows that direct marketing, sales promotion and price perception have a positive and significant effect on consumer buying interest in the Indosat Ooredoo internet data package. While partially it shows that direct marketing and sales promotion have a significant influence on buying interest. While the perception of price has no significant effect on consumer buying interest in the Indosat Ooredoo internet data package Keywords: Direct marketing, sales promotion, price perception and buying interest.